The impact of director gender on European firms' M&A activity - Lundstroem, Joakim Magnus Gunnar (2016)
Academic literature in finance and economics indicates that women are different from men in their choices and preferences. Women are generally viewed as being less overconfident and more risk averse than men, but little is known about how gender impacts decisions in the context of mergers and acquisitions (M&A) in Europe. In this dissertation I examine if the female behavioral traits influence the firms´ acquisition behavior. I test the hypothesis whether female directors, being less overconfident, overestimate less the gains from mergers. Under this hypothesis, female directors are expected to be less likely to initiate an acquisition bid. Conditionally on bidding, they are expected to pay a lower bid premium for the target firm. This study finds that each female director relates to approximately 13% more bids. However, the hypothesis regarding the impact of director gender on the size of bid premium could not be tested. The fraction of females on the board is statistically insignificant, hence, it could not be statistically confirmed that there exists a negative association between the fraction of female directors on the acquiror board and the size of the bid premium paid for the acquisition.